2022
DOI: 10.3390/ijerph192113745
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of High-Intensity Interval Training in Cardiac Rehabilitation

Abstract: As global quality of life has improved, the risk factors for cardiovascular diseases have gradually increased in prevalence. People have consequently sought to improve their health through physical exercise. High-intensity interval training (HIIT) is a cardiac rehabilitation (CR) tool that has been of great interest for several years. However, its feasibility and safety remain controversial. This study aimed to explore hot research topics and new directions regarding the role of HIIT in CR and to describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Most of the studies presented in Table 1 investigated the impact of highand moderate-intensity aerobic interval training on CVD patients (Rognmo et al, 2004;Rankin et al, 2012;Madssen et al, 2014;Kim, Choi, & Lim, 2015;Cardozo, Oliveira, & Farinatti, 2015;Conraads et al, 2015;Donelli da Silveira et al, 2020;Liu, Liu, Ji, Dai, & Han, 2022). Some studies showed that highintensity interval training, ranging from 80-95% HRmax, induced significant improvements in VO 2 max ranging from 13-22% after a 6- (Kim et al, 2015), 10-12- (Rognmo et al, 2004;Rankin et al, 2012;Madssen et al, 2014;Conraads et al, 2015;Donelli da Silveira et al, 2020) and16-20-(Cardozo et al, 2015;Liu et al, 2022) week experimental programme. Since all the studies showed significant cardiorespiratory adaptations it can be noted that the intensity variable plays crucial role in achieving those adaptations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies presented in Table 1 investigated the impact of highand moderate-intensity aerobic interval training on CVD patients (Rognmo et al, 2004;Rankin et al, 2012;Madssen et al, 2014;Kim, Choi, & Lim, 2015;Cardozo, Oliveira, & Farinatti, 2015;Conraads et al, 2015;Donelli da Silveira et al, 2020;Liu, Liu, Ji, Dai, & Han, 2022). Some studies showed that highintensity interval training, ranging from 80-95% HRmax, induced significant improvements in VO 2 max ranging from 13-22% after a 6- (Kim et al, 2015), 10-12- (Rognmo et al, 2004;Rankin et al, 2012;Madssen et al, 2014;Conraads et al, 2015;Donelli da Silveira et al, 2020) and16-20-(Cardozo et al, 2015;Liu et al, 2022) week experimental programme. Since all the studies showed significant cardiorespiratory adaptations it can be noted that the intensity variable plays crucial role in achieving those adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth mentioning that the studies presented in this paragraph also compared high-and moderate-intensity exercises. Considering the cardiorespiratory adaptations of moderate-intensity groups, improvements in VO 2 max ranged from 8-20% after a 6- (Kim et al, 2015), 10-12-(Rognmo et al, 2004Rankin et al, 2012;Madssen et al, 2014;Conraads et al, 2015;Donelli da Silveira et al, 2020) and16-20-(Cardozo et al, 2015;Liu et al, 2022) week experimental programme. Both high-and moderate-intensity exercise programme showed significant improvements in VO 2 max, although high-intensity interval training seemed to induce a slightly higher increment in cardiorespiratory indications than moderate training in CVDs patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric analysis offered an intuitive and effective foundation for integrating information, reflected interconnections between them, and predicted the development of cutting-edge advances in the area based on publications in this field ( 17 , 18 ). Recently, bibliometric analysis was widely adopted by scholars in neurology ( 19 ), vaccination ( 20 ), and otorhinolaryngology ( 21 ) related to COVID-19, especially the bibliometric analysis based on VOSviewer and CiteSpace software ( 22 , 23 ). However, bibliometric analysis of innate immunity in COVID-19 remains lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[15] It is primarily based on co-citation theory and uses a Pathfinder algorithm to accurately capture the evolutionary critical paths and knowledge inflection point of the target scientific field. [16] CiteSpace can present the development process and structural relationship of a research topic in the form of images, because it has the dual nature and characteristics of "graph and "spectrum." [17] Therefore, a graphic visualization as well as the network, structure, and derivation of many hidden complex relationships between knowledge units or clusters can be presented.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] It is primarily based on co-citation theory and uses a Pathfinder algorithm to accurately capture the evolutionary critical paths and knowledge inflection point of the target scientific field. [ 16 ] CiteSpace can present the development process and structural relationship of a research topic in the form of images, because it has the dual nature and characteristics of “graph and “spectrum.” [ 17 ] Therefore, a graphic visualization as well as the network, structure, and derivation of many hidden complex relationships between knowledge units or clusters can be presented. [ 18 ] This study used CiteSpace to systematically analyze the literature on ESWT for tendinopathies in terms of publication trends and characteristics of the core authors, highly cited literature, journals, and keywords, to examine research hotspots and trends in ESWT for tendinopathies.…”
Section: Introductionmentioning
confidence: 99%